2023
DOI: 10.1002/adhm.202300842
|View full text |Cite
|
Sign up to set email alerts
|

Polyglycerol‐Based Biomedical Matrix for Immunomagnetic Circulating Tumor Cell Isolation and Their Expansion into Tumor Spheroids for Drug Screening

Abstract: Circulating tumor cells (CTCs) are established as distinct cancer biomarkers for diagnosis, as preclinical models, and therapeutic targets. Their use as preclinical models is limited owing to low purity after isolation and the lack of effective techniques to create 3D cultures that accurately mimic in vivo conditions. Herein, a two‐component system for detecting, isolating, and expanding CTCs to generate multicellular tumor spheroids that mimic the physiology and microenvironment of the diseased organ is propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…As assessed by TEM and NTA, the isolation procedure did not exert significant impact on the LT-EV morphology and size distribution, suggesting that the properties of these Ti-EVs were largely maintained. Indeed, with advantages of potent specificity and efficiency, the immunomagnetic separation assay based on immunomagnetic particles has been acknowledged as a powerful system for the enrichment of target marked cells [32, 33]. Utilization of this approach in the EV research will benefit the in-depth biological and mechanistic investigations of endogenous Ti-EVs, as well as t diagnostic and therapeutic applications.…”
Section: Discussionmentioning
confidence: 99%
“…As assessed by TEM and NTA, the isolation procedure did not exert significant impact on the LT-EV morphology and size distribution, suggesting that the properties of these Ti-EVs were largely maintained. Indeed, with advantages of potent specificity and efficiency, the immunomagnetic separation assay based on immunomagnetic particles has been acknowledged as a powerful system for the enrichment of target marked cells [32, 33]. Utilization of this approach in the EV research will benefit the in-depth biological and mechanistic investigations of endogenous Ti-EVs, as well as t diagnostic and therapeutic applications.…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective for this hydrogel is to maintain a stable and durable crosslinked structure that can securely hold the encapsulated cells within a 3D network for an extended period until a noticeable increase in their size is observed. The gel stiffness and consistency were influenced by the previous study from our group [28]. In the former study, we showed that cancer cell MCF7 could grow well in a 3D softer texture gel matrix whose shear storage modulus or stiffness is approximately in the range of 0.1-0.7 kPa and they successfully formed multicellular tumor spheroids (MCTSs) after the incubation for roughly 2 weeks.…”
Section: Synthesis Of Gel Precursors and Hydrogel Formationmentioning
confidence: 96%
“…The hydrogel created with dPG alpha-acrylate and 4-arm PEG thiol is typically nondegradable, primarily because of its ether and thioether linkages. This is in contrast to our earlier studies, where we employed degradable hydrogels linked by acrylate groups containing degradable ester bonds [28,30]. To prove the degradation concept, we, therefore, performed the degradation study for 2 weeks by using the hydrogel candidate without encapsulating cells.…”
Section: Characterizations Of Hydrogelmentioning
confidence: 99%
“…The main principle for MCTS formations is to resist interaction between cell and substrate, and promote coupling between cells. [ 183b ] Liquid overlay applied by low adhesive surface coating of substrates, [ 184 ] or hanging‐drop culturing of cell suspension on the underside of culture vessel lids, [ 185 ] are the two main strategies to initialize spheroid fabrication, which stimulates cell aggregation and proliferation, resulting in the generation of 3D cultured tumor spheroids [ 186 ] (Figure 10B,C). Sharing similar histological structures with solid tumors, MCTS have been dedicated to research into cell proliferation and differentiation, cell cycle, intercellular communication, and of course, therapeutic orientations in solid tumors for a long time, and was first introduced for in vitro investigation of NDC since 2004.…”
Section: Novel Physiological Models Mimicking the In Vivo Np Cellular...mentioning
confidence: 99%
“…C) Bright‐filed images illustrating the development of a 3D tumor spheroid from immunomagnetically isolated cancer cells. Reprinted with permission, [ 186 ] Copyright 2023, Wiley‐VCH. D) Fluorescence images of cryosections of co‐cultured spheroids (FaDu human pharynx squamous cell carcinoma and CAF granular fibroblasts) after incubated with different mTHPC‐loaded nanovesicles.…”
Section: Novel Physiological Models Mimicking the In Vivo Np Cellular...mentioning
confidence: 99%